Cryptocurrency di Tengah Norma Keagamaan: Studi tentang Persepsi Risiko dan Kepatuhan Syariah terhadap Minat Penggunaan di Kalangan Mahasiswa Muslim Kota Parepare - Rizal; Damirah (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
This study examines the impact of risk perception and Sharia compliance on the intention to use cryptocurrency among Muslim students in Parepare City. With the rapid development of digital currencies such as Bitcoin and Ethereum, concerns regarding their compliance with Islamic principles and the high volatility associated with them have emerged, particularly among religious communities. Utilizing a quantitative approach, data were collected from 88 respondents of youth muslim in parepare city. The research employs multiple regression analysis to assess the influence of both independent variables on students' willingness to adopt cryptocurrency. The results indicate that both risk perception and Sharia compliance significantly influence the intention to use cryptocurrency, with Sharia compliance having a slightly stronger effect. Furthermore, the study reveals that uncertainty regarding the religious legitimacy of cryptocurrency increases perceived risk, thus reducing interest in its adoption. These findings highlight the importance of addressing religious and ethical considerations in the acceptance of new financial technologies within Muslim communities. This research contributes to the growing body of literature on Islamic finance and provides insights for policymakers and financial institutions aiming to develop Sharia-compliant digital financial products. It also underscores the necessity for clearer religious guidelines on cryptocurrency to support informed financial decision-making among Muslim youth.